THERMOGRAVIMETRY ANALYSIS FOR DETERMINING THE ADSORPTION SELECTIVITY OF CARBON MOLECULAR SIEVE FROM OIL PALM SHELL - Herawan, Safarudin Gazali (2003)
A new method has been found for determining the adsorption selectivity between oxygen and nitrogen. Commonly, determination of adsorption selectivity used the isotherm adsorption and the adsorption rate method, no study on the carbon molecular sieve (CMS) using Thermogravimetry (TG) and Derivative Thermogravimetry (DTG) for defining the adsorption selectivity. TG and DTG method basically was used to measure the weight loss subjected to function of temperature. In this method, it is found that the sample, which was prepared by mixing phenol, formaldehyde and bituminous compound with the char of oil palm shell shows a good selectivity for oxygen; hence, it is expected to be useful for the separation of nitrogen from oxygen (air), and this result also shows a good agreement with the result from the adsorption rate method that has been done by another work.